Synthesis of mullite whiskers - Choi, HJ; Lee, JG (AMER CERAMIC SOC, 2002)
Mullite whiskers were synthesized by heating a mixture of SiO2 and silicon in an alumina tube reactor under a flow of H-2 and CF4. The length and diameter of the whiskers were several hundred micrometers and > 15 mum, respectively. It was postulated that a vapor phase reaction between SiF4 and AlF3 made possible the synthesis of the large mullite whiskers.
Keywords: SILICON-CARBIDE WHISKERS; SIC WHISKERS; MICROSTRUCTURE; GROWTH